THE EFFECT OF NUTRITION EDUCATION TO PROSPECTIVE BRIDE IN PREGNANCY NUTRITION PREPARATION TO PREVENT THE RISK OF STUNTING: STUDY LITERATURE REVIEW - Ratna Wulandari; Ahmad Syafiq (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The National Strategy Program in Indonesia for the Acceleration of Stunting Prevention targets specific nutrition interventions for Women of Reproductive Age. The government implemented a health examination program for prospective brides to prevent the risk of stunting. This study aims to describe the implementation of nutrition education for brides in Indonesia, and its effect on knowledge, attitudes, and consumption behavior of nutritious food as a preparation for a healthy pregnancy. The method of this research is Systematic Literature Review by screening articles using the PRISMA chart. The article sources used were Google Scholar and Garuda with article years 2020 to 2022, 333 articles were found, and 16 articles were required to be reviewed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method. Description of research results is the locations used to provide education include the Office of Religious Affairs (Kantor Urusan Agama), Puskesmas, and local area halls. The educational media used are booklets, leaflets, digital applications, social media, and PowerPoint presentations. The nutrition materials given were 1000 HPK, preconception nutrition, and anemia prevention. The results of the study provided nutrition education had a significant impact on knowledge and attitudes, but education would have an impact on behavior if it was given at least 3 times. This study concludes that the nutrition education strategy needs to include factors that affect education acceptance such as educational background and social economy, and the impact assessment of education must also include the behavior of consuming nutritious food and changes in the body's nutritional status.